Does carbon emissions trading promote green technology innovation in China? - Zhang, Wei; Li, Guoxiang; Guo, Fanyong (Applied energy, 2022)
•Carbon emissions trading inhibits green technology innovation in the short run.•Carbon emissions trading will reduce the carbon emissions and carbon intensity greatly at this stage.•Carbon emissions trading has a crowding-out effect on R&D investment and increases the carbon trading price, which inhibited green technology innovation.•It is necessary to control the scale of carbon emission quota and diversify the subjects of carbon trading. Carbon emissions trading is an important measure to promote high-quality economic development. Based on the panel data of 30 provincial administrative regions in China from 2008 to 2017, this paper uses the difference-in-differences method to analyze the impact of carbon emissions trading on green technology innovation. The results show that: (1) Carbon emissions trading inhibits green technology innovation in the current stage, but greatly reduces carbon emissions and carbon intensity; (2) Carbon price and R&D investment are the mainly working channels, carbon emissions trading has a crowding-out effect on corporates’ R&D investment and increases the carbon trading price, which in turn inhibits green technology innovation; (3) Carbon emissions trading has a stronger inhibitory effect on green technology innovation in eastern regions and regions with low emission intensity. Local government competition positively moderates the green technology innovation effect of carbon emissions trading. However, the command-controlled environmental regulations and the scale of the carbon emission quota have opposite effects, with the compatibility of environmental regulation tools remaining to be resolved. Therefore, it is necessary to control the scale of carbon emission quota to diversify the subjects of carbon trading and strengthen the impact of market-incentive environmental regulation tools.